2009
DOI: 10.2478/v10042-008-0069-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-transfection of EYFP-GH and ECFP-rab3B in an experimental pituitary GH3 cell: a role of rab3B in secretion of GH through porosome.

Abstract: Abstract:Recently, in order to elucidate the role of rab3B in porosome, we have observed the incorporation of rab3B in the secretion of GH through porosome under confocal laser scanning microscopy (CLSM). Transfected cells with GH-EYFP fusion protein and rab3B-ECFP fusion protein were observed under CLSM, which showed the colocalization of EYFP-GH and ECFP-rab3B in the budding configuration of secretory process. These structural and functional images of rab3B imply the incorporation of rab3B in the secretion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Long-distance transport of these vesicles is regulated by kinesin-driven transport [15], [16] and posttranslational modifications, such as tyrosination [17] and polyglutamylation [18]. When the vesicles come to the terminal points, the process is passed to the exocytotic mechanisms [19], [20], [21]. Phosphatidylinositol plays critical roles in this exocytotic step [22].…”
Section: Introductionmentioning
confidence: 99%
“…Long-distance transport of these vesicles is regulated by kinesin-driven transport [15], [16] and posttranslational modifications, such as tyrosination [17] and polyglutamylation [18]. When the vesicles come to the terminal points, the process is passed to the exocytotic mechanisms [19], [20], [21]. Phosphatidylinositol plays critical roles in this exocytotic step [22].…”
Section: Introductionmentioning
confidence: 99%
“…Our studies and studies from other laboratories (Craciun and Barbu-Toduran, 2013; Elshennay, 2011; Hammel and Meilijson, 2012; Japaridze et al, 2012; Matsuno et al, 2008; Okuneva et al, 2012; Paredes-Santos et al, 2012; Savigny et al, 2007; Siksou et al, 2007) established porosomes to be secretory portals that perform the specialized task of fractional discharge of intravesicular contents from cells during cell secretion. The significance of the porosome discovery is reflected by several publications involving its structure (Craciun and Barbu-Toduran, 2013; Elshennay, 2011; Hammel and Meilijson, 2012; Japaridze et al, 2012; Matsuno et al, 2008; Okuneva et al, 2012; Paredes-Santos et al, 2012; Savrgny et al, 2007; Siksou et al, 2007), and the associated transient fusion mechanism (Aravanis et al, 2003; Taraska et al, 2003; Thorn et al, 2004) accompanied by fractional discharge of intravesicular contents from cells. Studies in endocrine cells report secretory granules to be recaptured largely intact following stimulated exocytosis (Taraska et al, 2003); in neurons, single synaptic vesicles fuse transiently and successively without loss of vesicle identity (Aravanis et al, 2003); and in the exocrine pancreas, secretion is characterized by long fusion pore openings and preservation of secretory vesicle lipid identity (Thorn et al, 2004).…”
Section: Introductionmentioning
confidence: 58%
“…Furthermore in a previous study (Abu-Hamdah et al 2006) using photonic force microscopy, we reported ZGs tethered at the cell plasma membrane in live pancreatic acinar cells, which also demonstrates that ZGs are tethered and are on a railroad system for precise delivery to its destination and not randomly free-floating as previously thought. It is interesting to note that even though both the nuclear pore complex and the porosome in exocrine pancreas are about the same size (120 nm on average), the number of nuclear pores in a single nucleus is approximately 100 times more abundant than the number of porosomes (Cho et al 2007Drescher et al 2011;Elshennawy 2011;Lee et al 2009;Matsuno et al 2008;Okuneva et al 2011;Paknikar and Jeremic 2007;Savigny et al 2007;Siksou et al 2007;Zhao et al 2010) in a single pancreatic acinar cell, the nuclear pores are difficult to visualize in electron micrographs. Similarly, neuronal porosomes measuring 10-15 nm too are difficult to observe in electron micrographs, however are easily observed at the nerve terminals using the AFM .…”
Section: Porosomes With Docked Secretory Vesiclesmentioning
confidence: 99%
“…Subsequent studies over the years demonstrated unequivocally the presence of porosomes in all secretory cells, including endocrine cells, neuroendocrine cells, hair cells, astrocytes, and neurons, and therefore the porosome came to be recognized as the universal secretory portal in cells (Cho et al 2002a, b;Cho et al 2004Cho et al , 2005aCho et al , 2007Cho et al , 2008Drescher et al 2011;Elshennawy 2011;Jena 2012;Jena et al 2003;Jeremic et al 2003;Lee et al 2009;Matsuno et al 2008;Okuneva et al 2011;Paknikar and Jeremic 2007;Savigny et al 2007;Schneider et al 1997;Siksou et al 2007;Zhao et al 2010). Similarly, in vivo and in vitro measurements of secretory vesicle dynamics using the AFM demonstrated that vesicle swelling occurs during secretion, which is required for the expulsion of intravesicular content from cells during the process .…”
Section: Introductionmentioning
confidence: 99%